2018
DOI: 10.1002/jrs.5351
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of monosaccharides studied by Raman scattering

Abstract: We report a Raman spectroscopy study of glucose, fructose, and mannose. The spectra have been recorded for the dry powders and for solutions in H2O and D2O and commented in the so‐called “fingerprint region” of the spectra (200–1,400 cm−1), in order to study the influence of the interaction with water on the solute vibrational modes. We have evidenced splitting of some bands, due to the presence of different anomers in solution. The isotopic substitution of the solvent has allowed in some instances to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Figure 5A shows an overlay of the reference OCA spectra and cartilage at a depth of 100 μm. Dominant OCA peaks are present at 1003 cm −1 from symmetric CcN stretching in urea, [ 23 ] 628 cm −1 from D‐(−)‐fructose CCO 5 groups, and 524 cm −1 from the pyranose ring in D‐(−)‐fructose [ 24 ] among others. Figure 5B shows the postclear stage MCR deconvolutions, illustrating where OCA peaks coincide with other sub‐components.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5A shows an overlay of the reference OCA spectra and cartilage at a depth of 100 μm. Dominant OCA peaks are present at 1003 cm −1 from symmetric CcN stretching in urea, [ 23 ] 628 cm −1 from D‐(−)‐fructose CCO 5 groups, and 524 cm −1 from the pyranose ring in D‐(−)‐fructose [ 24 ] among others. Figure 5B shows the postclear stage MCR deconvolutions, illustrating where OCA peaks coincide with other sub‐components.…”
Section: Resultsmentioning
confidence: 99%
“…Ruggiero et al used Raman to study the hydration of the monosaccharides glucose, fructose, and mannose. They found that glucose and fructose interact strongly with water, whereas for mannose, a weaker interaction with water and a different behaviour of its anomers, was observed . Xu and co‐workers used Raman and quantum chemistry calculations to probe the structural organization of N ‐methyl‐2‐pyrrolidinone in binary mixtures .…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…They found that glucose and fructose interact strongly with water, whereas for mannose, a weaker interaction with water and a different behaviour of its anomers, was observed. [181] Xu and co-workers used Raman and quantum chemistry calculations to probe the structural organization of N-methyl-2-pyrrolidinone in binary mixtures. [182] Zhu and co-workers performed Raman measurements and ab initio quantum chemical calculations of ion association behaviour in calcium nitrate solution.…”
Section: Metals Carbons and Other Crystalline Materialsmentioning
confidence: 99%
“…The Raman spectroscopy study of hydration of a series of monosaccharide such as glucose, fructose, and mannose pointed out the contribution provided by this spectroscopy technique for probing the hydration shell structure in these systems. The analysis of Raman spectra recorded for the dry powders and for solutions of monosaccharides in H 2 O and D 2 O revealed the presence of a characteristic “fingerprint region” where the spectral changes of some vibrational bands were interpreted as signature of the influence of the interaction with water.…”
Section: Hydration In Biological Moleculesmentioning
confidence: 99%